Brazilian society for angiology and vascular surgery guidelines on abdominal aortic aneurysm - Mulatti, Grace Carvajal (2023)
The Brazilian Society of Angiology and Vascular Surgery, through the Guidelines Project, presents new Abdominal Aortic Aneurysm Guidelines, on the subject of care for abdominal aortic aneurysm patients. Its development prioritized descriptive guidelines, using the EMBASE, LILACS, and PubMed databases. References include randomized controlled trials, systematic reviews, meta-analyses, and cohort studies. Quality of evidence was evaluated by a pair of coordinators, aided by the RoB 2 Cochrane tool and the Newcastle Ottawa Scale forms. The subjects include juxtarenal aneurysms, infected aneurysms, and new therapeutic techniques, especially endovascular procedures. The current version of the guidelines include important recommendations for the primary topics involving diagnosis, treatment, and follow-up for abdominal aortic aneurysm patients, providing an objective guide for medical practice, based on scientific evidence and widely available throughout Brazil.